2022
DOI: 10.3390/fishes7030110
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Culture Period and Stocking Density on Input Demand and Scale Economies of Milkfish (Chanos chanos) Polycultures with White Shrimp (Penaeus indicus)

Abstract: Milkfish, Chanos chanos, is one of the major inland cultured fish species in Taiwan. Variations in land resources and climate have led to the application of two distinct culture practices of milkfish polycultures with white shrimp, Penaeus indicus. This study applies a translog cost function model to analyze the production scale economy and input demand price elasticity of four milkfish polyculture systems with two different culture periods (OWC and NOWC) and two different white shrimp–milkfish fry stocking ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Acanthurus sp., Carcharhinus melanopterus, Scarus sp., Rhinoptera sp., Lepidochelys olivacea, and T. blochii are common species in the collections of various public aquariums [92], [93]. While C. chanos dan T. blochii aquaculture and consumption species [94], [95]. The biota collection is divided into 5 IUCN conservation statuses, labelled LC.…”
Section: Lepidochelys Olivacea Vulnerable (Vu) Carnivoramentioning
confidence: 99%
“…Acanthurus sp., Carcharhinus melanopterus, Scarus sp., Rhinoptera sp., Lepidochelys olivacea, and T. blochii are common species in the collections of various public aquariums [92], [93]. While C. chanos dan T. blochii aquaculture and consumption species [94], [95]. The biota collection is divided into 5 IUCN conservation statuses, labelled LC.…”
Section: Lepidochelys Olivacea Vulnerable (Vu) Carnivoramentioning
confidence: 99%
“…In the early stage, Taiwan's milkfish farming mainly adopted the monoculture method. Later, it was found that a mixed culture with white shrimp (Penaeus indicus) (Figure 2) could not only increase owner's income [1][2][3][4], but also keep fish ponds clean [4][5][6]. However, the cultivation of white shrimp comes with many advantages, such as removing the need for extra feed and cleaning feed residues and fish waste without affecting the growth space needed for milkfish.…”
Section: Introductionmentioning
confidence: 99%
“…clean [4][5][6]. However, the cultivation of white shrimp comes with many advantages, such as removing the need for extra feed and cleaning feed residues and fish waste without affecting the growth space needed for milkfish.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation